Corporate financialization : an economic sociology perspective - Do Carmo, Marcelo José, 1973-; Sacomano Neto, Mário; Donadone, Julio Cesar (Routledge frontiers of political economy, 2023)
"The economic process of financialization is defined by many as the development of the dependence and subordination of the productive sector to the financial sector. Leading to an emphasis on maximising shareholder value above all else, the financialization of the economy and production has an enormous impact on the everyday life of ordinary people including the erosion of employment right, the rise of precarious work, and rising inequalities. Using multi-case study research and an exploratory approach, this book analyzes the financialization process in the ten companies with the highest market capitalization worldwide including tech firms, oil companies and banks. This book analyzes indicators of financialization in large corporations including a comparison between profitability sources; shareholding structure, acquisitions and sales of shares; mergers and acquisitions; the origins of directors; payment of compensation to executives; dividend payments to shareholders and stock repurchases; employee salaries; and employment levels. The data demonstrates that what would once have been considered non-core business activities have become more profitable than core business activities in many of these companies. In some cases, these companies are responsible for large investment funds and financial-type institutions which already surpass the largest banks in terms of assets under management. Meanwhile, the average salaries at some of these companies have been falling in real terms due to the rise of outsourcing and the use of cheap or precarious labour. Adopting an economic sociology approach, this book marks a significant contribution to the literature on financialization in economics, sociology and business"--